2011
DOI: 10.1111/j.1750-3841.2011.02427.x
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil of Curcuma longa Inhibits Streptococcus mutans Biofilm Formation

Abstract: Curcuma longa (C. longa) has been used as a spice in foods and as an antimicrobial in Oriental medicine. In this study, we evaluated the inhibitory effects of an essential oil isolated from C. longa on the cariogenic properties of Streptococcus mutans (S. mutans), which is an important bacterium in dental plaque and dental caries formation. First, the inhibitory effects of C. longa essential oil on the growth and acid production of S. mutans were tested. Next, the effect of C. longa essential oil on adhesion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 21 publications
2
30
0
1
Order By: Relevance
“…While many essential oils which contain β-sesquiphellandrene have been shown to possess anti-microbial and anti-oxidant activities [22], [27], the effect may be caused by other components of the essential oil especially in cases where β-sesquiphellandrene is found only in minute amounts. Denyer et al [21], however, showed that among α-zingiberene, β-sesquiphellandrene and β-bisabolene from the essential oils of ginger, β-sesquiphellandrene had the highest antirhinoviral activity with an IC 50 of 0.44 µM in the plaque reduction test [21].…”
Section: Resultsmentioning
confidence: 99%
“…While many essential oils which contain β-sesquiphellandrene have been shown to possess anti-microbial and anti-oxidant activities [22], [27], the effect may be caused by other components of the essential oil especially in cases where β-sesquiphellandrene is found only in minute amounts. Denyer et al [21], however, showed that among α-zingiberene, β-sesquiphellandrene and β-bisabolene from the essential oils of ginger, β-sesquiphellandrene had the highest antirhinoviral activity with an IC 50 of 0.44 µM in the plaque reduction test [21].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, previous study has revealed the anti-biofilm potency of YSMP against the biofilm-positive strain, S. epidermidis ATCC 35984 (Chusri, Settharaksa et al 2013). Even though the anti-biofilm activity of YSMP and its components on mastitis-causing bacteria has never been investigated, curcumins and essential oil of C. longa displayed antibiofilm potencies on Streptococcus mutans (Lee et al 2011), Vibrio spp. (Packiavathyet al 2013), and P. aeruginosa (Rudrappa & Bais 2008), while, α-mangostin has been reported to have an activity against streptococci (Nguyen & Marquis 2011). 3.3.…”
Section: Biofilm Inhibition Potency Of Ysmp and Its Componentsmentioning
confidence: 99%
“…Turmeric has also been widely used in ayurvedic medicine for its anti-microbial, anti-oxidant, anti-inflammatory astringent, anti-septic and analgesic properties. [26] Lee et al demonstrated that an essential oil isolated from Curcuma longa efficiently inhibited S. mutans species which is important microflora in formation of dental plaque and dental caries. [27] Curcumin, a major curcumanoid found in the spice turmeric, exhibits anti-inflammatory properties against Porphyromonas gingivalis which is considered as major periodontopathic bacterium.…”
Section: Aloe Barbadensis (Aloe Vera)mentioning
confidence: 99%